Rheumatoid meningitis: A systematic review and meta‐analysis. (29th June 2021) - Villa, Eduardo; Sarquis, Teresita; de Grazia, José; Núñez, René; Alarcón, Pablo; Villegas, Rodrigo; Guevara, Carlos
Abstract: Background and purpose: Rheumatoid meningitis (RM) is a neurological complication of rheumatoid arthritis (RA). Current evidence is based on case reports and partial reviews. Methods: This is a systematic review and meta‐analysis following the PRISMA statement. The aim is to describe the characteristics of the disease, including clinical, imaging and laboratory findings, treatment, outcomes and prognosis reported in the literature. Results: In all, 103 studies with 130 cases were included. RM affected adults with an average age of 62 years, with or without a previous RA diagnosis. RA activity and time with the disease were associated with a worse prognosis. Most common clinical manifestations were transient focal neurological signs (64.6%), systemic symptoms (51.3%), episodic headache (50.4%) and neuropsychiatric alterations (47.7%). Joint manifestations were present in only 27.4% of cases. Brain magnetic resonance imaging showed unilateral or bilateral involvement, predominantly frontoparietal. Both pachymeninges and leptomeninges were affected, the latter more frequently (82.88%). The laboratory findings included increased levels of rheumatoid factor (89.71%), anti‐cyclic citrullinated peptide (89.47%), C‐reactive protein (82.54%) and erythrocyte sedimentation rate (81.81%). Cerebrospinal fluid analysis showed an increase in the protein level (76.14%), with pleocytosis (85.19%) of mononuclear predominance (89.19%). Biopsy was performed in 72.52% of the patients. Corticosteroid pulse therapy was the main induction therapy. Disease relapse occurred in 31.17% of patients, whilst 54.54% had a full recovery. Conclusions: Rheumatoid meningitis must be considered in adult patients with or without RA diagnosis, high‐dose corticosteroid induction therapy should be installed and maintenance therapy plays a key role. It is not recommended to use anti‐TNF as an induction therapy. Nowadays, RM has a significantly better outcome. These findings may aid clinicians in timely RM diagnosis and treatment, thus improving its outcomes. Abstract : Rheumatoid meningitis is a neurological complication of rheumatoid arthritis, with current evidence based on case reports. This is the first systematic review and meta‐analysis following the PRISMA statement. These findings may aid clinicians in timely diagnosis and treatment, thus improving outcomes.